Rethinking the Structures of Academic Writing in the Times of Exacerbated Inequity: An Introduction - Zwagerman, Sean; Mitchell, Kim M. (Discourse and Writing/Rédactologie, 2022)
An introduction to the special issue for Rethinking the Structures of Academic Writing in the Times of Exacerbated Inequity. This paper presents a discussion of the inspiration for this special call for papers, an analysis of the genre presentation of the typical critical examination of problems emerging from social inequities, and a summary of each of the papers contained within the special issue.